The Extreme Flood Capacity of Al-Majjarah Canal and Regulator Within Al-Ramadi Project System - Al-Tameemi, Amro; Al-Thamiry, Hayder (Al-Nahrain Journal for Engineering Sciences, 2023)
It is essential to review and develop a system of water control structures and canals that can be used to manage high-flow discharges and the flood control plan requirement to modify the system's capacity. Al-Ramadi Project System is considered one of the main flood control projects on the Euphrates River within Anbar Governorate, Western Iraq. This study will focus on Al-Majjarah Canal and Regulator, which is part of Al-Ramadi Project and has the function of a link canal between Al-Habbaniyah and Al-Razazza lakes, and describe the capacity of the canal under typical operating conditions and during floods. The study used HEC-RAS 6.1 software to run a numerical model to simulate this canal. According to previous research studies near the research region on the Euphrates River, for the main canal, the roughness coefficient was taken at 0.026, and for the flood plain, it was taken at 0.03. The same parameter value was applied to Al-Majjarah Canal. Due to the study region's similar geology and nature. Moreover, a sensitivity analysis was made of the roughness coefficient and its influence on the water surface elevation for the canal. The model result indicated in the current situation of Al-Majjarah Canal can pass a flow rate of 1300 m3/s when Al-Razazza Lake is at an average water level that has been approved by the Ministry of Water Resources at 32.02 m.a.m.s.l.. If the water level in Al-Razazza Lake is in the semi-filled position of 40 m.a.m.s.l., it causes floods for the canal because the water level rises above the banks of the canal at the last kilometer from the canal, even when passing a few discharges through the canal. Accordingly, it is not possible to safely pass the flow rate for a flood wave with a 500-year return period predicted by the "Study of Strategy for Water and Land Resources in Iraq (2014)", which is 2000 m3/s for this canal, without making modifications to the expansion of Al-Majjarah Regulator by adding additional gates, expanding the entrance and exit of the Regulator, reshaping and expanding some cross-sections, and raising some of the banks for the canal. The above-mentioned modification were applied for the purpose of passing the expected discharge from the canal, while maintaining a freeboard of 1 m between the water surface and the canal banks.